2011
DOI: 10.1186/1743-0003-8-59
|View full text |Cite
|
Sign up to set email alerts
|

Objective assessment of motor fatigue in multiple sclerosis using kinematic gait analysis: a pilot study

Abstract: BackgroundFatigue is a frequent and serious symptom in patients with Multiple Sclerosis (MS). However, to date there are only few methods for the objective assessment of fatigue. The aim of this study was to develop a method for the objective assessment of motor fatigue using kinematic gait analysis based on treadmill walking and an infrared-guided system.Patients and methodsFourteen patients with clinically definite MS participated in this study. Fatigue was defined according to the Fatigue Scale for Motor an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 45 publications
1
44
0
Order By: Relevance
“…A few studies have investigated the effects of walking-induced fatigue on the variability of gait kinematics in people with MS. Crenshaw et al found no change in kinematic or kinetic variability following a fatiguing walk in 20 people with MS [17], while a pilot study by Sehle et al reported some increased kinematic variability in individual patients following walking at preferred speed to the point of exhaustion on a treadmill [18]. It is unclear whether these inconsistent findings in kinematic variability might be due to differences in the distance walked, as these were not documented in either study.…”
mentioning
confidence: 47%
“…A few studies have investigated the effects of walking-induced fatigue on the variability of gait kinematics in people with MS. Crenshaw et al found no change in kinematic or kinetic variability following a fatiguing walk in 20 people with MS [17], while a pilot study by Sehle et al reported some increased kinematic variability in individual patients following walking at preferred speed to the point of exhaustion on a treadmill [18]. It is unclear whether these inconsistent findings in kinematic variability might be due to differences in the distance walked, as these were not documented in either study.…”
mentioning
confidence: 47%
“…Within this framework, Sehle et al 26 as well as Phan-Ba et al 11 proposed calculation methods for quantifying the magnitude of walking-related motor fatigue in PwMS during treadmill and overground walking, respectively. The latter study expressed walking speed at the end of the timed 500-m walk test (T500MW) as a fraction of the walking speed obtained from a short walking test (Timed 25-foot Walk Test, T25WT) to derive a deceleration index (DI).…”
Section: Introductionmentioning
confidence: 99%
“…The pattern of knee hyperextension was slightly greater when fatigued with the FES on which may have been done to further compensate for eccentric demands imposed on the knee extensors which are likely to have been weakened further after the fatiguing walk [21]. Poor knee control has been shown to correlate with fatigue [19] and has been shown to deteriorate with walking induced fatigue [18,40]. This avoidance pattern leads to slightly reduced power absorbed at the knee of the more affected limb.…”
Section: Initial Orthotic Effect Of Fesmentioning
confidence: 99%